2022
DOI: 10.5144/0256-4947.2022.75
|View full text |Cite
|
Sign up to set email alerts
|

Intracoronary epinephrine versus adenosine in the management of refractory no-reflow phenomenon: a single-center retrospective cohort study

Abstract: BACKGROUND: The no-reflow phenomenon is associated with a considerable reduction in myocardial salvage in patients with ST elevation myocardial infarction (STEMI) treated by primary percutaneous intervention (PCI). There has been no head-to-head comparison of intra-coronary epinephrine to adenosine in the management of no-reflow phenomenon. OBJECTIVES: Evaluate the short- and long-term efficacy and safety of using intracoronary epinephrine versus adenos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
3

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 21 publications
0
20
0
3
Order By: Relevance
“…We identified 646 articles in the initial search. After removal of duplicates ( n = 116) and excluding ineligible articles (title / abstract: n = 498, full-text: n = 28) and addition of two citations from the Google Scholar survey, six articles met our inclusion criteria; included studies focused on efficacy and safety of IC epinephrine as a first-line treatment ( n = 2) 6 , 11 or after failure of other conventional agents ( n = 4) 7 10 for the treatment of patients with no-reflow phenomenon. Studies were conducted in Egypt ( n = 2), Poland ( n = 1), Pakistan ( n = 1), the United States ( n = 1), and Turkey ( n = 1) ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We identified 646 articles in the initial search. After removal of duplicates ( n = 116) and excluding ineligible articles (title / abstract: n = 498, full-text: n = 28) and addition of two citations from the Google Scholar survey, six articles met our inclusion criteria; included studies focused on efficacy and safety of IC epinephrine as a first-line treatment ( n = 2) 6 , 11 or after failure of other conventional agents ( n = 4) 7 10 for the treatment of patients with no-reflow phenomenon. Studies were conducted in Egypt ( n = 2), Poland ( n = 1), Pakistan ( n = 1), the United States ( n = 1), and Turkey ( n = 1) ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Darwish et al 8 conducted the second cohort study in 2022 and found that a higher percentage of patients who were treated with IC epinephrine achieved successful reperfusion (TFG = 3) compared with those with IC adenosine (69.1% versus 52.7%, respectively; p value = 0.04). During hospitalization, sustained ventricular tachycardia was observed in one of the patients in the epinephrine group.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations